Profile Of Cancer Cases at A Tertiary Care Level Teaching Hospital in Rural Western Maharashtra, India - Deshpande, Jayant D; Singh, Kailash K; Phalke, Deepak B (National Journal of Community Medicine, 2012)
Background: Cancer is one of the major public health problems worldwide. Prevalence and pattern of cancer is known to vary from region to region. Epidemiological information on cancer including the pattern is an important basis for determining the priorities for cancer control in any population group. Objective: Present work is an attempt to study magnitude, profile and some epidemiological aspects in relation to cancer cases at a tertiary care level teaching hospital in rural area. Method: All records were studied and analyzed. A total of 1106 patients were treated during the period studied. A proforma was used to collect data such as age, sex, place of residence, type of cancers and treatment given. The data collected were entered into MS-Excel sheets and analysis was carried out. The information obtained was tabulated analyzed using the software GraphPad Instat demo version. Results: A total of 1106 cancer patients were treated during the January 2010 to December 2010. Among these, 626(56.60) were females and 480(43.39) were females. In males, the common cancers were oral cavity cancers, lung cancers and GIT cancers. The most common cancers among females were the cervical carcinomas, which constituted 32.10% of the total number of cancers cases followed by cancers of breast. Almost 2/3rd of cases occurred in the age group of 41 to 70 years. Maximum frequency was observed in 51–60 year age group in both sexes. Maximum numbers (74.59%) of the cases were from rural area. The main methods of cancer treatment were surgery, chemotherapy and radiotherapy, used alone or in combination. Conclusion: Tobacco and alcohol related cancers predominated in males. In females, cervical cancer predominated over breast cancer. Human behavior is a major determinant in the successful control of cancer. Understanding cancer magnitude, risk and trends will be of help in cancer control.